The use of psychotropic medications in the nursing team - Viegas, Graziela Lenz; Lima, Juliana da Silva; Pigatto, Bruno; Souza, Luciana Pereira Tarrago de; Nascimento, Patrícia do; Mari, Sidia de (Seven Editora, 2023)
The evolution of nursing has been accompanied by the emergence of diseases, especially around mental health. The use of psychotropic medications is the alternative for the treatment of these diseases. The objective of this study is to analyze the use of psychotropic medications in the nursing team and its consequences. This is a literature review, systematic and reflexive, using the descriptors Nursing, Psychotropic Medications and Patient Safety, using the online database. The use of psychotropic substances by nursing professionals is not recent, one of the hypotheses for this habit is the various personalities that make up the nursing team and the risk they are exposed to daily.  Anxiety, stress, and sleep disturbances are one of the symptoms that affect these professionals. The use of psychotropic drugs is one of the treatments used for these symptoms, however, these drugs end up being used indiscriminately by nursing professionals, due to the knowledge acquired in the exercise of their profession in relation to these medications, harming the safety of the patient and the professional. It is concluded that the use of psychotropic drugs is not restricted to the hospital area, the absence of supervision of the sale and supply of these drugs does not restrict access, without the need for a medical prescription. The supervision of the use of psychotropic medications, as well as their side effects and the damage they can cause, and finally, therapies aimed at the dependence of these medications, is an alternative to the abusive use of these drugs. DOI:https://doi.org/10.56238/innovhealthknow-041